HUBUNGAN JARAK MONITOR, DURASI PENGGUNAAN KOMPUTER, TAMPILAN LAYAR MONITOR, DAN PENCAHAYAAN DENGAN KELUHAN KELELAHAN MATA - Dessy Widhya Putri; Mulyono Mulyono (The Indonesian Journal of Occupational Safety and Health, 2018)
The use of the computer was very support various human activities. Although many of the benefits gained from computer but if we weren’t awareness can cause health problem, such as complaints of eye fatigue. The purpose of this research was to find the relation between distance monitor, duration of computer use, screen display monitor and lighting with complaints of eye fatigue on workers at PT. Indonesia Power UP Semarang. This research was a quantitative research with cross sectional design. Population in this research was all of workers at PT Indonesia Power UP Semarang as many as 280 peoples. Samples was taken by purposive sampling method with some defined criterias until gained 77 people. The instruments used in this research were questionnaires, meter, and lux meter. Univariate analysis performed using the proportion to clarify the prevalence of subjective complaints of eye fatigue and factors related to complaints of eye fatigue, while the bivariate analysis performed by chi-square test (X2) with a significant level of 5%. Result showed that 80,5% had subjective complaints of eye fatigue. Chi square test result were Pvalue of monitor distance variable was 0.499, pvalue of screen display monitor variable was 0.016, pvalue of duration of computer use variable was 0.018 and pvalue of lighting variable was 1.000. The conclution of this research was from the four variables only two which related significantly with complaints of eye fatigue on workers PT. Indonesia Power UP Semarang were duration of computer use and screen display monitor. Keywords: complaints of eye fatigue, computer users, duration of computer use